Engineering aspects of shape memory alloys - Duerig, T. W. (Butterworth-Heinemann, 1990)
Engineering Aspects of Shape Memory Alloys provides an understanding of shape memory by defining terms, properties, and applications. It includes tutorials, overviews, and specific design examples-all written with the intention of minimizing the science and maximizing the engineering aspects. Although the individual chapters have been written by many different authors, each one of the best in their fields, the overall tone and intent of the book is not that of a proceedings, but that of a textbook. The book consists of five parts. Part I deals with the mechanism of shape memory and the alloys.